Pengujian Serbuk Tuba (Derris elliptica) Untuk Mengendalikan Nematoda Puru Akar (Meloidogyne spp.) Pada Tanaman Seledri - Siti Raudah; Elly Liestiany; Lyswiana Aphrodyanti (www.ulm.ac.id, 2026)
Celery (Apium graveolens L.) is a horticultural commodity with high export value, was susceptible to attack by root knot nematodes (Meloidogyne spp.) which causes root swelling and reduced yields. Farmers often use chemical control, but it risks polluting the environment. This research aims to assess the effectiveness of tuba powder (Derris elliptica) as an environmentally friendly vegetable pesticide. A one-factor Completely Randomized Design (CRD) was used with five treatments and four replications (a total of 60 plants), namely control and tube powder doses of 5, 10, 15 and 20 g, each of which was inoculated with 500 L2 Meloidogyne spp larvae. The results showed that all doses of tuba powder suppressed nematode attacks significantly; a dose of 20 g produced the lowest intensity (10.00%) compared to the control (71.67%). This effectiveness is thought to be related to the rotenone which is antifeedant and neurotoxic, so tuba powder has the potential to be a sustainable and environmentally friendly control of NPA.